The Implementation of Maqāṣid Al-Syarīʻah by Mediator Judges in Divorce Mediation at the Watampone Religious Court Class 1A - Margono, Farhan; Rahmawati, St; faturahman, faturahman (Al-Syakhsiyyah: Journal of Law and Family Studies, 2025)
This research aims to analyze the application of the principles of maqāṣid al-syarīʻah by mediator judges in the mediation process of divorce cases at the Class 1A Watampone Religious Court.  The principles that make the application of the five basic maqāṣid al-syarīʻah (ḥifẓ al-dīn, ḥifẓ al-nafs, ḥifẓ al-‘aql, ḥifẓ al-nasl, and ḥifẓ al-māl) internalized in the mediation strategy and approach by the mediator judge to maintain the integrity of the household and prevent divorce. This research uses a qualitative approach with a field study design. Data was collected through interviews, observation and documentation, then analyzed using Miles and Huberman's interactive model. The results of the study indicate that although mediation has great potential in reducing divorce rates, its effectiveness is highly dependent on the competence of the mediator judge and the emotional readiness of the parties. The principle of maqāṣid al-syarīʻah is used by the mediator judge as a value-oriented mediation approach from the beginning of the mediation process until the divorce trial process becomes a reflection to avoid harm, promote peace and consider the socio-spiritual impact on children. However, the effectiveness of conflict resolution still requires institutional support and ongoing training for mediators. Therefore, this study recommends strengthening the capacity of mediator judges through contextual and solution-based maqāṣid training to create a more beneficial and long-term oriented mediation approach.